Mussel-inspired multifunctional supramolecular hydrogels with self-healing, shape memory and adhesive properties. Issue 34 (11th August 2016) - Li, Zhaowen; Lu, Wei; Ngai, To; Le, Xiaoxia; Zheng, Jing; Zhao, Ning; Huang, Youju; Wen, Xiufang; Zhang, Jiawei; Chen, Tao
Abstract : A novel multifunctional supramolecular hydrogel with self-healing, shape memory and adhesive properties is successfully developed on the basis of dynamic phenylboronic acid (PBA)–catechol interactions. Abstract : A novel multifunctional supramolecular hydrogel with self-healing, shape memory and adhesive properties is successfully developed on the basis of dynamic phenylboronic acid (PBA)–catechol interactions. The reversible nature of PBA–catechol bonds renders the hydrogel with outstanding self-healing and shape memory behavior, and the mussel-inspired catechol moieties generate fascinating adhesive properties.